Factors Influencing Economic Growth in ASEAN Countries 1999-2019 - Eric Andrawina, Kevin; Aisyah Tri Rahayu, Siti; Hakim, Lukman (Lafadz Jaya Publisher, 2024)
This research focuses on how technology, human capital, and investment influence economic growth in ASEAN countries from 1999 to 2019. This research uses panel data regression analysis. The research results show that technology has a significant positive effect on economic growth. Meanwhile, human capital has a significant negative effect on economic growth and investment has no significant effect on economic growth.